Improving problems solving skills through problem-based learning of oil palm empty fruit bunch waste in science learning for students at SMAN 1 Muara Badak - Sasmitha, Hijrana Mega; Kusumaningtyas, Pintaka; Erika, Farah; Sumarioto, Sumarioto (Faculty of Teacher Training and Education, Mulawarman University, 2024)
Problem-solving skills need to be provided to students so that they can play a role in overcoming environmental problems in everyday life. This study aims to determine the effect of problem-based learning in science learning on the topic of empty oil palm bunches waste to improve students' ability to solve problems. This research is quantitative research with a pre-experimental method. The research design used is a one-group pretest-posttest design with five replications. The samples in this study were students of SMAN 1 Muara Badak in grade . Data collection used tests in the form of pre-tests and post-tests. Data analysis used the N-Gain Test. The results showed an increase in problem-solving skills in the good category. Thus, it can be concluded that problem-based learning of oil palm empty fruit bunches waste in science learning can improve students' skills to solve environmental problems in everyday life.